Analisis Empiris Pengaruh Implementasi Pendidikan Agama Islam terhadap Moderasi Beragama dan Karakter Mahasiswa di Perguruan Tinggi Islam - M. Miftakhul Huda (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
Islamic Religious Education plays a strategic role in strengthening religious moderation and student character within the context of religious universities, especially in addressing the challenges of extremism, social polarization, and the moral degradation of the younger generation. Theoretical studies show that the structured implementation of Islamic Religious Education is capable of strengthening the values of tolerance, social ethics, and personal integrity. This research aims to analyze the implementation of Islamic Religious Education in strengthening religious moderation and student character at IAI Al-Fatimah Bojonegoro, focusing on pedagogical strategies, value internalization, and student learning experiences. The research method uses a quantitative-descriptive approach with the population being all active students, while the sample consists of 162 students selected using proportional random sampling. The research instrument was a Likert-scale questionnaire that had been tested for validity (r = 0.612–0.834) and reliability (α = 0.912). Data analysis included descriptive statistics and linear regression. The research results indicate that the implementation of Islamic Religious Education significantly influences religious moderation (β = 0.547; t = 8.214; p = 0.000) and student character (β = 0.603; t = 9.011; p = 0.000). The research model has strong explanatory power with an R² value of 0.299 for religious moderation and 0.364 for student character. The research conclusion confirms that Islamic Religious Education functions as an effective transformative pedagogical framework in strengthening religious moderation and shaping student character in Islamic higher education institutions.